Public knowledge towards implementation of GST in Kota Samarahan / Ahmad Zharif Mohammad Khalid and Wan Mohd Muaz Mohd Navawi - Mohammad Khalid, Ahmad Zharif; Mohd Navawi, Wan Mohd Muaz (2014)
Goods and Service Tax (GST) is mechanism financial taxation systems that want to be adopt in our taxation system nowadays by our government early April 2015. For the last few years, we still using Sale and Service Tax (SST) which is taxation system that been practice from early independent. Due to that, Datuk Seri Najib Tun Abdul Razak as our Prime Minister, has introduce GST which he believe it will become catalyzer of an effective mechanism toward nation development. The study examines the public knowledge towards the implementation of GST at Kota Samarahan. It has involved publics around Kota Samarahan area which consist of various backgrounds in term of race, religion, education and age. This study involved a random sample of 398 respondents which come from many layers of public. Based on our study, it shows that most of the respondents still do not aware about the implementation of GST as they only know about the words of GST but does not know on the meaning and the purpose or impact when this kind of policy being implemented soon. It also shows that, sources of information which related to newspaper, television, radio and internet does not help them in making them understand about GST. It is due to this policy does not implemented yet which they still not feel the impact of this policy. Besides, some of them believe that the implementation of GST will cause price hiking which involved with all items although government has announced that there are certain products especially crucial products and service will not being imposed with GST. The study also shows that the level of understanding and readiness of public is only at medium level. It has urged the publicity of this policy must be more grand and aggressive which involve with non-government and government itself to promote this policy more details to public. It is very important as it will ensure that public will concern about the purpose of government in implementing this policy which they still need more time in preparing their knowledge before this policy being implemented.